An Optical Coherence Tomography-Based Deep Learning Algorithm for Visual Acuity Prediction of Highly Myopic Eyes After Cataract Surgery - Wei, Ling; He, Wenwen; Wang, Jinrui; Zhang, Keke; Du, Yu; Qi, Jiao; Meng, Jiaqi; Qiu, Xiaodi; Cai, Lei; Fan, Qi; Zhao, Zhennan; Tang, Yating; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Due to complicated and variable fundus status of highly myopic eyes, their visual benefit from cataract surgery remains hard to be determined preoperatively. We therefore aimed to develop an optical coherence tomography (OCT) based deep learning algorithms to predict the postoperative visual acuity of highly myopic eyes cataract surgery. Methods: The internal dataset consisted of 1,415 highly myopic eyes having cataract surgeries in our hospital. Another external dataset consisted of 161 highly myopic eyes from Heping Eye Hospital. Preoperative macular OCT images were set as the only feature. The best-corrected visual acuity (BCVA) at 4 weeks after surgery was set as the ground truth. Five different deep learning algorithms including ResNet-18, ResNet-34, ResNet-50, ResNet-101, and Inception-v3 were used to develop the model aiming at predicting the postoperative BCVA and an ensemble learning were further developed. The model was further evaluated in the internal and external test datasets. Results: The ensemble learning showed the lowest mean absolute error (MAE) of 0.1566 logMAR and lowest root mean square error (RMSE) of 0.2433 logMAR in the validation dataset. Promising outcomes in the internal and external test datasets were revealed with MAEs of 0.1524 and 0.1602 logMAR, and RMSEs of 0.2612 and 0.2020 logMAR, respectively. Considerable sensitivity and precision were achieved in the BCVA < 0.30 logMAR group, with 90.32% and 75.34% in the internal test dataset, and 81.75% and 89.60% in the external test dataset, respecitively. The percentages of the prediction errors within ±0.30 logMAR were 89.01% in the internal, and 88.82% in the external test dataset. Conclusions: Promising prediction outcomes of postoperative BCVA was achieved by the novel OCT-trained deep learning model, which will be helpful for the surgical planning of highly myopic cataract patients.